Scary movie 4 - Bierko, Craig; Pullman, Bill.; Anderson, Anthony, 1970-; Faris, Anna, 1976-; Nielsen, Leslie, 1926-; Zucker, David, 1947- ([Del Mar, CA] : The Weinstein Company : Distributed by Genius Products, 2006)
Dim-witted Cindy Campbell and her self-serving, sex-crazed pal Brenda are joined by Tom Ryan, a cute, but utterly clueless guy as together, they battle to save the world from a ruthless alien invasion. Cindy also discovera a house is haunted by a little boy and goes on a quest in the village to find out who killed him and why.
Based on the characters created by Shawn Wayans, Marlon Wayans, Buddy Johnson, Phil Beauman, Jason Friedberg, & Aaron Seltzer.
Special features: Tom Ryan on Oprah - the long take; Visual effects piece; Deleted and extended scenes; The man behind the laugh (with director David Zucker); Feature commentary with David Zucker, Bob Weiss, and Craig Mazin.
Director of photography, Thomas E. Ackerman ; editors, Craig Herring, Tom Lewis ; music, James L. Venable ; costume designer, Carol Ramsey ; production designer, Holger Gross ; visual effects supervisors, Mat Beck, Ray McIntyre Jr.
Anna Faris, Craig Bierko, Bill Pullman, Anthony Anderson, Carmen Electra, Chris Elliott, Kevin Hart, Cloris Leachman, Michael Madsen, Dr. Phil McGraw, Leslie Nielsen, Shaquille O'Neal, Molly Shannon.
DVD, region 1; Dolby Digital 5.1 surround.
English or dubbed French dialogue, Spanish subtitles; closed-captioned.